The Experience of Living With Bowel Cancer for Māori in Taranaki - Ruakere, Brian Thomas (Auckland University of Technology, 2016)
The title of this study is: The experience of living with bowel cancer for Māori in Taranaki. Research methods for this study have been adapted from research approaches collectively known as Kaupapa Māori. The study is also informed by Gadamerian hermeneutic interpretive methodology which unpacks the nature of how we understand and interpret. However, the lens through which understanding is expressed, is from a Māori worldview. Ten Māori patients, diagnosed with bowel cancer were interviewed and their narratives analysed using Gadamerian hermeneutic methodology. The concepts of whakapapa, mauri and tapu were fundamental to the analysis process. Whakapapa in the context of this study examined the stories substance or origin about participant experiences and initial signs that not all was right with their health. The concept of mauri shed light on ways of experiencing bowel cancer that came to reveal how participant stories fell into one of three perspectives: mauri moe; mauri oho and mauri ora. Signs archetypal of mauri moe were evident where participant behaviours remained grounded in responses framed within the notion of mamae and its negative elements of neglect, hurt, pain, anguish, and sorrow. Mauri oho revealed distinct changes in behavioural patterns that signified an upsurge in motivation by participants who were committed to overcome their dilemma and be well again. Mauri ora signified actions that revealed successful outcomes when participants became highly motivated, felt good about their health and were committed to keeping good health. The concept of tapu was utilised to examine the underlying principal issues that determined participant existence in the present. The findings showed that participants had no understanding of bowel cancer before they were diagnosed. Some participants experienced shame and embarrassment at the prospect of having to live the rest of their lives with a stoma. Recognition of tapu through the proper exercise of mana was an important factor in participant recovery. Violation of tapu through the wrongful exercise of mana also manifested as having negative effects on participant recovery. Based on the findings from this study the following recommendations for further research are proposed: a Kaupapa Māori action research study in conjunction with introducing the inflatable colon to the community working with a group of stakeholders to educate Māori about bowel cancer and; a Kaupapa Māori action research study with a group of stakeholders to devise a treatment pathway that integrates the concepts of whakapapa, mauri and tapu when assessing Māori who present to healthcare providers with a suspected prognosis of bowel cancer.
Keywords: Bowel Cancer and Maori; Bowel Cancer and Indigenous; Maori and Health Literacy; Maori and Cancer